Complementary Ramsey Numbers - Akihiro Munemasa; Masashi Shinohara (IndoMS, 2019)
In this paper, we consider a variant of Ramsey numbers which we call complementary Ramsey numbers (m,t,s). We first establish their connections to pairs of Ramsey (s,t)-graphs. Using the classification of Ramsey (s,t)-graphs for small s,t, we determine the complementary Ramsey numbers (m,t,s) for (s,t)=(4,4) and (3,6).